1991
DOI: 10.1016/0143-4160(91)90042-d
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate displaces inositol 1,4,5-trisphosphate (IP3) from its receptor and inhibits IP3 induced Ca2+ release in permeabilized pancreatic acinar cells

Abstract: -Inositol 1,4,5-trisphosphate (IP3) induced Ca 2 + release in digitonin permeabllized rat pancreatic acinar cells is specifically inhibited by decavanadate. The ca 2 + release induced with 0.18 flM IP3 is half maximally inhibited with approximately 5 flM decavanadate. Complete inhibition is achieved with around 20 flM decavanadate. Removal of decavanadate from the permeabilized cells fully restores sensitivity towards IP3, indicating the reversibility of the inhibition. Oligovanadate, which inhibits A TP depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 31 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…The action of decavanadate can be overcome by increasing the concentration of IP 3 , suggesting competition for the IP 3 binding site [115], an observation that is confirmed by radioligand binding experiments where decavanadate inhibits the specific binding of [ 3 H]IP 3 to IP 3 R with low micromolar affinity [117]. Such activity appears unique to decavanadate as other vanadate compounds, such as orthovanadate and oligovanadate, have no effect on IP 3 binding or IP 3 -induced Ca 2+ release, even at high concentrations [116][117]. Likewise, decavanadate has no effect on SERCA-driven Ca 2+ uptake, whereas oligovanadate is a potent inhibitor of this Ca 2+ pump.…”
Section: Decavanadatementioning
confidence: 76%
See 1 more Smart Citation
“…The action of decavanadate can be overcome by increasing the concentration of IP 3 , suggesting competition for the IP 3 binding site [115], an observation that is confirmed by radioligand binding experiments where decavanadate inhibits the specific binding of [ 3 H]IP 3 to IP 3 R with low micromolar affinity [117]. Such activity appears unique to decavanadate as other vanadate compounds, such as orthovanadate and oligovanadate, have no effect on IP 3 binding or IP 3 -induced Ca 2+ release, even at high concentrations [116][117]. Likewise, decavanadate has no effect on SERCA-driven Ca 2+ uptake, whereas oligovanadate is a potent inhibitor of this Ca 2+ pump.…”
Section: Decavanadatementioning
confidence: 76%
“…The polyoxoanion, decavanadate, is a well known inhibitor of IP 3 -induced Ca 2+ release in a variety of cell types with an IC 50 of ~5 M [115][116]. The action of decavanadate can be overcome by increasing the concentration of IP 3 , suggesting competition for the IP 3 binding site [115], an observation that is confirmed by radioligand binding experiments where decavanadate inhibits the specific binding of [ 3 H]IP 3 to IP 3 R with low micromolar affinity [117].…”
Section: Decavanadatementioning
confidence: 99%
“…In vitro experiments showed that V 10 inhibits myosin ATPase, SR calcium ATPase, and SR calcium release induced by the second messenger inositol triphosphate (IP3) [51,98,134]. Importantly, decavanadate inhibits both the contractile system and the regulation of muscle contraction.…”
Section: Decavanadate Interactions and Effects In Proteinsmentioning
confidence: 97%
“…Myosin is a protein that plays a pivotal role in ATPdriven Ca 2+ -dependent muscle contraction and it was found that docking of decavanadate stabilizes it against break-down to monovanadate(V). In vitro experiments showed that V 10 inhibits myosin ATPase, SR Ca 2+ -ATPase, and SR Ca 2+ release induced by the second messenger inositol triphosphate (IP3) [364] [365] [366]. Moreover, decavanadate inhibits both the contractile system and the regulation of muscle contraction.…”
Section: Myosinsmentioning
confidence: 99%